2010
DOI: 10.1177/0021998310369592
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Porous Materials for Dental Applications

Abstract: New hybrid polymer-ceramic obturation materials were developed using synthetic hydroxyapatite, two different types of ceramic particles, and a polymer with a high agglutination capacity, high abrasion resistance, and good adhesion to the dentin. Silica nano-particles of 16 nm and alumina micro-particles of 3.2 μm were used: this difference in sizes allows a better packing of the particles into the resin rendering in an improvement in the mechanical and abrasion properties. The resin reacts with the dentin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Sprio et al 19 stated that the addition of limited amounts of TiO 2 as reinforcing phase (20 vol%) resulted optimal to confer high values of flexural strength, fracture toughness and limited elastic modulus, in the typical range of values manifested by cortical bone. Estevez et al 20 conducted research on new hybrid materials and developed it using two different types of ceramic particles (silica and alumina) with different sizes (16 and 3.2 mm). The results of above study on 75% alumina observed the highest abrasion resistance and best mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Sprio et al 19 stated that the addition of limited amounts of TiO 2 as reinforcing phase (20 vol%) resulted optimal to confer high values of flexural strength, fracture toughness and limited elastic modulus, in the typical range of values manifested by cortical bone. Estevez et al 20 conducted research on new hybrid materials and developed it using two different types of ceramic particles (silica and alumina) with different sizes (16 and 3.2 mm). The results of above study on 75% alumina observed the highest abrasion resistance and best mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In this case, the mechanical properties and the abrasion and the scratching resistance were increased by the addition of two different types of particles with different sizes: alumina microparticles and silica nanoparticles. 27 The use of ceramic particles with different sizes allows the filling, with nanoparticles, of the interstitial space left by the microparticles; the use of micro-and nanoparticles produces a reinforcement of the composite that renders in materials with improved mechanical and tribological properties. 28,29 The mixture of polyisocyanate with the resin and the ceramic particles is a reactive system because the polyisocyanate reacts with all OH groups present in the system.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the amount of ceramic particles that can be introduced into the polymer is larger with respect to the former case. 27 In this work, new ceramic-polymers porous hybrid materials were synthesized with the appropriated morphology to be used as prosthesis or implants in living organism. The materials were added with two different types of ceramic particles of different sizes to improve the mechanical and tribological properties of the final material.…”
Section: Introductionmentioning
confidence: 99%